Determination of the Traditional and Complementary Medicine Methods Used by Parents for Their 7-14-Year-Old Children with Upper Respiratory Tract Infection and Their Attitudes - Murat Bektaş; Şenay Demir; Dilek Demir Kösem (Sakarya Tıp Dergisi)
Background: Traditional and complementary medicine methods are used by parents in children with upper respiratory tract infections, and parents should be informed about the side effects that may occur due to these methods. This study was conducted to determine the traditional and complementary medicine methods utilized by parents for their 7-14-year-old children with upper respiratory tract infections and their attitudes. Method: A descriptive research design was used. The study was conducted between November 2023 and January 2024. Data were collected using a “Socio-Demographic Data Form” and the “Attitude towards Holistic Complementary and Alternative Medicine Scale.” A total of 310 parents participated in the study online. Results: The rate of parents’ use of traditional and complementary medicine in children with upper respiratory tract infections was 91.6%. These methods that parents most frequently used were showering the child or tepid sponging in case of fever, giving the child milk with honey, ginger, molasses in case of sore throat, washing the child’s nose with salt water in case of nasal congestion, putting a hot towel on the child’s ear in case of earache, and giving the child honey-molasses to reduce/cut the cough. Parents’ mean score on the Attitude towards Holistic Complementary and Alternative Medicine Scale was found to be 29.51±3.79. As the age of the child (β=1.258) and the economic status of the family (β=2.916) increased, parents’ use of traditional and complementary medicine increased, as well. Conclusion: The majority of parents used traditional and complementary medicine methods for their 7-14-year-old children who had upper respiratory tract infections. It was determined that parents’ attitudes towards traditional and complementary medicine methods were positive and moderate.